Legal Protection for Victims of Dating Violence (Semarang State University Undergraduate Law and Society Review, 2022)
Violence against women is rife, also in romantic relationships. However, a romantic relationship (dating) is different from a marriage relationship which has a clear legal basis. Thus, women often experience violence and are not accommodated in adequate protection. This study aims to analyze the legal protection for victims of dating violence. This study uses a normative juridical and comparative law approach. This study finds that in essence, protection for victims of dating violence has been regulated, although not explicitly in various legal regulations ranging from the protection of women, the Human Rights Act, to the Criminal Code.